2021
DOI: 10.1007/s00170-021-07163-7
|View full text |Cite
|
Sign up to set email alerts
|

3D printing: rapid manufacturing of a new small-scale tidal turbine blade

Abstract: The 3D printing technology used for small tidal and wind turbines has great potential to change and overcome certain weaknesses in traditional manufacturing techniques. In rural areas and isolated communities, small turbine systems could be locally fabricated and assembled by using additive manufacturing machines and also can be employed to decrease residential energy consumption. The objective of the paper is to study the thermomechanical performance of 3D printing of a small-scale tidal turbine blade and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…conducted a study of the AM of small tidal turbine blades and examined the conceptual considerations, including the material properties and aerodynamic parameters. [ 149 ] This study showed a high potential for the AM of small tidal turbine blades, but more investigations are necessary to qualify this application. In addition to the structural applications of PAEKs products, they can also be used for functional applications by compounding with other materials.…”
Section: Potential Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…conducted a study of the AM of small tidal turbine blades and examined the conceptual considerations, including the material properties and aerodynamic parameters. [ 149 ] This study showed a high potential for the AM of small tidal turbine blades, but more investigations are necessary to qualify this application. In addition to the structural applications of PAEKs products, they can also be used for functional applications by compounding with other materials.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…AM-processed PAEK products are not limited to applications in the biomedical, aerospace, and electronic fields, but also exhibit potential in other important applications, such as molds, small-scale tidal turbine blades, engine manifolds, and neutron shielding. [84,149,150] It was demonstrated that a ME-printed CF/PEEK mold tooling insert can replace the traditional costly metal insert to print short production runs of acrylonitrile, butadiene, styrene, polystyrene, and rubber components. [84,151] The insert maintained its mechanical integrity and the injection molded components presented the correct dimensions and the same level of mechanical properties as their counterparts fabricated using a traditional metal mold.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Computational 3D printing based on Digimat-AM techniques have been used to developed a new small-scale tidal turbine blade [204]. The Digimat-AM tool was used to simulate different configurations and to evaluate the performance of parts fabricated by 3D printing.…”
Section: Additive Manufacturing In Emerging Energy and Electronic Dev...mentioning
confidence: 99%
“…The fabrication of such turbines can be achieved through advanced techniques like 3D printing or additive manufacturing (AM) [8][9][10] , facilitating the automated construction of 3D components by layering base materials and overcoming limitations in molding fabrication methods [11,12] . Rouway et al [13] investigate the viability of employing 3D printing technology, specifically Selective Laser Sintering (SLS), to create compact tidal turbine blades suitable for deployment in rural regions. The study focuses on utilizing specific polymers and reinforcements in the printing process, the research evaluates thermomechanical performance, revealing differences in warpage among materials.…”
Section: Introductionmentioning
confidence: 99%